MODEL PROJECT BASED LEARNING SECARA DARING MENGUNAKAN SOFTWARE CAM MATA PELAJARAN TEKNIK PEMESINAN CNC/ CAM - Muhamad Kamaludin; Dadang Hafid; Heri Setiawan (DESANTA (Indonesian of Interdisciplinary Journal), 2022)
The Covid19 pandemic condition demands the implementation of social restrictions, including in the field of education, including the limitation of face-to-face activities in the learning process, the current situation of the learning process is carried out online (in the network), so a new pedagogical approach is needed, appropriate learning media, with design and simulation in the learning process so as to optimize student learning outcomes. The learning model that is estimated to be suitable for learning CNC and CAM machining techniques is the Project Based Learning (PJBL) model through the CAM software tool, namely Mastercam X5. The research method used is an experimental research method, with a pre-experimental design, one group pre-test-post-test design. The instruments used in the form of pre-test, post-test and jobsheet, it can be concluded that the learning process using the PJBL model through the Mastercam X5 software can be categorized as good, runs smoothly and orderly also has a positive and significant effect on improving student learning outcomes on CNC and CAM materials in SMK.